The delivery of injury prevention exercise programmes in professional youth soccer: Comparison to the FIFA 11+ - O`Brien, J.; Young, W.; Finch, C. F. (Journal of Science and Medicine in Sport, 2017)
Objectives Injury prevention exercise programmes for amateur soccer have gained considerable attention, but little is known about their relevance and adaptability to professional soccer settings. The first aim of this study was to evaluate the delivery and content of injury prevention exercise programmes used by professional youth soccer teams, compared to the industry standard injury prevention exercise programme for soccer, the Fédération Internationale de Football Association's FIFA 11+. The second aim was to document specific challenges to implementing injury prevention exercise programmes in this context. Design Prospective observational study. Methods The participants were soccer coaches, fitness coaches and physiotherapists (n = 18) from four teams in a professional youth soccer academy. Each team's chosen injury prevention exercise programmes were observed weekly across an entire soccer season (160 sessions). The delivery and content of the programmes were documented on a standardised worksheet and compared to the FIFA 11+. Specific implementation challenges were recorded. Results Fitness coaches were the primary deliverers of injury prevention exercise programmes, with support from physiotherapists. Multiple delivery formats and locations were employed, along with the extensive use of equipment. Across all injury prevention exercise programme sessions, a median of one FIFA 11+ exercise was performed in its original form and a further four in a modified form. Implementation challenges included poor staff communication, competing training priorities and heavy game schedules. Conclusions Although the basic components of the FIFA 11+ hold relevance for professional youth male teams, the delivery and content of injury prevention exercise programmes require considerable tailoring for this context. Recognising this will inform the development of improved, context-specific injury prevention exercise programmes, along with corresponding strategies to enhance their implementation.